Sequential transfection of RUNX2/SP7 and ATF4 coated onto dexamethasone-loaded nanospheres enhances osteogenesis - Hye Jin Kim (Nature Portfolio, 2018)
Abstract The timing of gene transfection greatly influences stem cell differentiation. Sequential transfection is crucial for regulation of cell behavior. When transfected several days after differentiation initiation, genes expressed at the late stage of differentiation can regulate cell behaviors and functions. To determine the optimal timing of key gene delivery, we sequentially transfected human mesenchymal stem cells (hMSCs). This method can easily control osteogenesis of stem cells. hMSCs were first transfected with RUNX2 and SP7 using poly(lactic-co-glycolic acid) nanoparticles to induce osteogenesis, and then with ATF4 after 5, 7, and 14 days. Prior to transfecting hMSCs with all three genes, each gene was individually transfected and its expression was monitored. Transfection of these genes was confirmed by RT-PCR, Western blotting, and confocal microscopy. The pDNAs entered the nuclei of hMSCs, and RUNX2 and SP7 proteins were translated and triggered osteogenesis. Second, the ATF4 gene was delivered when cells were at the pre-osteoblasts stage. To induce the osteogenesis of hMSCs, the optimal timing of ATF4 gene delivery was 14 days after RUNX2/SP7 transfection. Experiments in 2- and 3-dimensional culture systems confirmed that transfection of ATF4 at 14 days after RUNX2/SP7 promoted osteogenic differentiation of hMSCs.